Modified sodium ferrous sulfate positive electrode material as well as preparation method and application thereof

By loading carbon nanotube/ferro-based MOF composite and nickel-manganese sulfide on sodium ferrous sulfate positive electrode material, the shortcomings of existing materials in terms of specific capacity and cycling performance are solved, and the efficient charge transfer of sodium ion batteries is achieved and stability improvement.

CN119208571APending Publication Date: 2024-12-27HUAYOU NEW ENERGY TECH (QUZHOU) CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411370186.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing sodium ferrous sulfate positive electrode materials have shortcomings in taking into account specific capacity and circulation performance, and it is difficult to meet the actual needs of sodium ion batteries.

Method used

By loading carbon nanotube/ferro-based MOF composites and nickel-manganese sulfides on the sodium ferrous sulfate matrix, the molar ratio and preparation method are adjusted to increase the number of electrochemically active sites and sodium ion transport channels.

Benefits of technology

The charge transfer rate, structural stability and electronic conductivity of the positive electrode material are significantly improved, and the specific capacity and cycling performance of the battery are effectively improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208571A_ABST
    Figure CN119208571A_ABST
Patent Text Reader

Abstract

The invention discloses a modified sodium ferrous sulfate positive electrode material as well as a preparation method and application thereof, and relates to the technical field of sodium ion batteries. The modified sodium ferrous sulfate positive electrode material comprises a sodium ferrous sulfate matrix, and a carbon nanotube / iron-based MOF composite material and nickel manganese sulfide which are loaded on the sodium ferrous sulfate matrix. The structural stability and the electronic conductivity of the material can be remarkably improved by limiting the materials of the matrix and the load body, and the specific capacity and the cycle performance of the battery can be effectively improved by applying the positive electrode material to the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified sodium ferrous sulfate positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have attracted widespread attention due to their advantages such as low cost, high power and good stability. Among the positive electrode materials of sodium-ion batteries, polyanionic iron-based positive electrode materials are widely used due to their many advantages such as high structural stability and low cost. Among them, the sulfate in sodium ferrous sulfate is relatively stable and not easily oxidized or polymerized, so its electrochemical performance is also relatively stable. In recent years, with the increasing demand for portable devices and electric vehicle endurance, higher requirements have been placed on the specific capacity and cycle performance of sodium-ion batteries.

[0003] However, sodium ferrous sulfate itself has poor electronic conductivity, and its electrochemical capacity and cycle performance cannot meet the requirements of practical applications. It usually needs to be coated and modified on its surface to achieve performance optimization. However, the current single coating layer modification has limited effect, and it is difficult to take into account the improvement of both specific capacity and cycle performance.

[0004] Therefore, how to improve both the specific capacity and cycle performance of sodium ferrous sulfate is a technical problem to be solved urgently in this field. Summary of the invention

[0005] The main purpose of the present invention is to provide a modified sodium ferrous sulfate positive electrode material and a preparation method and application thereof, so as to solve the problem that it is difficult to improve both specific capacity and cycle performance in the prior art.

[0006] In order to achieve the above objectives, the first aspect of the present invention provides a modified sodium ferric sulfate positive electrode material, comprising a sodium ferrous sulfate matrix and a carbon nanotube / iron-based MOF composite material and nickel manganese sulfide loaded on the sodium ferrous sulfate matrix.

[0007] Furthermore, in the modified sodium ferrous sulfate positive electrode material, the molar ratio of the sodium ferrous sulfate matrix to the carbon nanotube / iron-based MOF composite material is 1:(0.03-0.08); and / or the molar ratio of the sodium ferrous sulfate matrix to the nickel manganese sulfide is 1:(0.03-0.05).

[0008] Furthermore, the carbon nanotube / iron-based MOF composite material includes carbon nanotubes and an iron-based MOF material synthesized in situ on the carbon nanotubes, wherein the molar ratio of the carbon nanotubes to the iron ions in the iron-based MOF material is (10-15):1.

[0009] Furthermore, the preparation method of the carbon nanotube / iron-based MOF composite material includes: mixing carbon nanotubes, organic ligands, ferric nitrate and an organic solvent, and performing heat treatment to in-situ synthesize the iron-based MOF material on the carbon nanotubes to obtain the carbon nanotube / iron-based MOF composite material.

[0010] Furthermore, the chemical formula of the sodium ferrous sulfate matrix is ​​Na2Fe2(SO4)3; the chemical formula of the nickel manganese sulfide is Ni x Mn y S2, where 0.5≤x≤0.9, 0.1≤y≤0.5.

[0011] Furthermore, the D50 particle size of the modified sodium ferrous sulfate positive electrode material is 3 to 8 μm.

[0012] The second aspect of the present invention provides a method for preparing the modified sodium ferrous sulfate positive electrode material provided in the first aspect, comprising the following steps:

[0013] Step S1, mixing carbon nanotubes, organic ligands, ferric nitrate and an organic solvent, and performing a first heat treatment to obtain a carbon nanotube / iron-based MOF composite material;

[0014] Step S2, mixing hexamethylenetetramine, nickel salt, manganese salt and water, and subjecting the mixture to a second heat treatment to obtain nickel-manganese-based hydroxide; mixing nickel-manganese-based hydroxide, sodium sulfide and water, and subjecting the mixture to a third heat treatment to obtain nickel-manganese sulfide;

[0015] Step S3, solid-phase mixing of the sodium source, ferrous sulfate, and ammonium sulfate, and sintering treatment to obtain a sodium ferrous sulfate material; mixing the sodium ferrous sulfate material, the carbon nanotube / iron-based MOF composite material, and the nickel manganese sulfide with water, and performing a fourth heat treatment to obtain a modified sodium ferrous sulfate positive electrode material.

[0016] Further, the organic ligand includes at least one of phthalic acid, isophthalic acid, and trimesic acid; and / or the organic solvent includes at least one of methanol, ethylene glycol, and N,N-dimethylformamide; and / or the nickel salt includes at least one of nickel nitrate, nickel acetate, and nickel sulfate; and / or the manganese salt includes at least one of manganese nitrate, manganese acetate, and manganese sulfate; and / or the sodium source includes at least one of sodium oxide, sodium hydroxide, sodium carbonate, and sodium nitrate.

[0017] Furthermore, the molar ratio of carbon nanotubes, ferric nitrate and organic ligand is (10-15):1:(0.8-1); and / or the molar ratio of hexamethylenetetramine, nickel salt and manganese salt is (10-15):1:(0.1-1); and / or the molar ratio of nickel manganese-based hydroxide and sodium sulfide is 1:(0.5-1); and / or the molar ratio of sodium element in the sodium source, ferrous sulfate and ammonium sulfate is (2.06-2.12):2:3; and / or the molar ratio of sodium ferrous sulfate, carbon nanotube / iron-based MOF composite material and nickel manganese sulfide is 1:(0.03-0.08):(0.03-0.05).

[0018] Further, the temperature of the first heat treatment is 60-100°C, and the time is 4-8 hours; and / or, the temperature of the second heat treatment is 60-100°C, and the time is 4-8 hours; and / or, the temperature of the third heat treatment is 140-200°C, and the time is 4-12 hours; and / or, the sintering treatment is carried out under an inert atmosphere at a temperature of 800-1200°C for 10-30 hours, and the inert atmosphere includes at least one of nitrogen and argon; and / or, the temperature of the fourth heat treatment is 40-60°C, and the time is 4-8 hours.

[0019] The third aspect of the present invention provides a sodium ion battery, comprising the modified sodium ferrous sulfate positive electrode material provided by the first aspect or the modified sodium ferrous sulfate positive electrode material prepared by the preparation method provided by the second aspect.

[0020] The implementation of the present invention has at least the following beneficial effects:

[0021] The modified sodium iron sulfate positive electrode material provided by the present invention can significantly increase the electrochemical active sites of the positive electrode material by limiting the materials of the matrix and the support, provide a large number of sodium ion transmission channels, effectively improve the charge transmission rate of the positive electrode material, improve the structural stability of the material, the sodium ion diffusion rate and the electronic conductivity, and apply the positive electrode material to a sodium ion battery, which can effectively improve the specific capacity and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope (SEM) image of the modified sodium ferrous sulfate positive electrode material in Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope (SEM) image of the positive electrode material in Comparative Example 1 of the present invention;

[0024] Figure 3 This is a scanning electron microscope (SEM) image of the positive electrode material in Comparative Example 3 of the present invention;

[0025] Figure 4This is a TEM image of the modified sodium ferrous sulfate positive electrode material in Example 1 of the present invention after 100 cycles under 2C conditions;

[0026] Figure 5 This is a TEM image of the positive electrode material in Comparative Example 1 of the present invention after 100 cycles under 2C conditions. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0028] As described in the background technology, it is difficult for existing sodium ferrous sulfate to improve both specific capacity and cycle performance. In order to solve the above technical problems, the first aspect of the present invention provides a modified sodium ferrous sulfate positive electrode material, including a sodium ferrous sulfate matrix and a carbon nanotube / iron-based MOF composite material and nickel manganese sulfide loaded on the sodium ferrous sulfate matrix.

[0029] In the modified sodium ferrous sulfate positive electrode material of the present invention, the matrix material is a sodium ferrous sulfate material, and the support material comprises a carbon nanotube / iron-based MOF composite material and nickel manganese sulfide.

[0030] Among them, carbon nanotube / iron-based MOF composite material refers to a material composed of carbon nanotubes and iron-based MOF, wherein the iron-based MOF is composed of iron ions or clusters connected to organic ligands by strong coordination bonds. The iron-based MOF has the same Fe-O bond as the matrix material, which can provide multiple electrochemically active sites and effectively improve the electrochemical capacity of the material. The carbon nanotube has a hollow tubular structure, which can provide a large number of sodium ion transmission channels and has a high conductivity. Under the joint action of carbon nanotubes and iron-based MOF, the introduction of the first carrier can significantly improve the sodium ion diffusion rate, electronic conductivity, thermal stability and chemical inertness of the positive electrode material, which helps to improve the specific capacity and cycle performance.

[0031] The carbon nanotubes may be single-walled carbon nanotubes or multi-walled carbon nanotubes, which are not specifically limited in the present invention.

[0032] Nickel manganese sulfide is a transition metal sulfide with a layered structure, which is conducive to the rapid and reversible deintercalation of sodium ions. At the same time, it has a transition metal-sulfur bond and can form a stable metal-sulfur bond with the matrix material. After sodium removal, it supports the sulfate lattice of the matrix, ensuring the structural stability and reversibility of the crystal structure during the reversible deintercalation process, which helps to improve the specific capacity and cycle performance.

[0033] According to the research of the present invention, the above-mentioned modified ferrous sulfate cathode material is applied to sodium ion batteries, which can effectively improve the specific capacity and cycle performance of the battery. This is because, on the one hand, by limiting the material of its matrix and support, the electrochemical active sites of the cathode material can be significantly increased, a large number of sodium ion transmission channels are provided, and the charge transfer rate of the cathode material is effectively improved. The structural stability of the material, the sodium ion diffusion rate and the electronic conductivity are improved, and the cathode material is applied to sodium ion batteries, which can effectively improve the specific capacity and cycle performance of the battery.

[0034] The present invention does not limit the specific loading amount of the support, as long as the material of the support is guaranteed. For example, in some embodiments, in the modified sodium ferrous sulfate positive electrode material, the molar ratio of the sodium ferrous sulfate matrix to the carbon nanotube / iron-based MOF composite material is 1: (0.03-0.08), such as 1: 0.03, 1: 0.05, 1: 0.08 or a range consisting of any two thereof; and / or, the molar ratio of the sodium ferrous sulfate matrix to the nickel manganese sulfide is 1: (0.03-0.05), such as 1: 0.03, 1: 0.04, 1: 0.05 or a range consisting of any two thereof.

[0035] The carbon nanotube / iron-based MOF composite material refers to a material composed of carbon nanotubes and iron-based MOF. In some embodiments, the carbon nanotube / iron-based MOF composite material includes carbon nanotubes and an iron-based MOF material synthesized in situ on the carbon nanotubes, wherein the molar ratio of the carbon nanotubes to the iron ions in the iron-based MOF material is (10-15):1, for example, 10:1, 12:1, 15:1 or a range consisting of any two of them.

[0036] Specifically, by limiting the iron-based MOF material to be synthesized in situ on the carbon nanotubes, it helps to improve the dispersion effect of the carbon nanotubes and the iron-based MOF material, thereby maximizing their advantages.

[0037] In the specific implementation process of the present invention, the preparation method of the carbon nanotube / iron-based MOF composite material includes: mixing carbon nanotubes, organic ligands, ferric nitrate and an organic solvent, and heating to in-situ synthesize an iron-based MOF material on the carbon nanotubes to obtain a carbon nanotube / iron-based MOF composite material.

[0038] In some embodiments, the chemical formula of the sodium ferrous sulfate matrix is ​​Na2Fe2(SO4)3; the chemical formula of the nickel manganese sulfide is Ni x Mn y S2, wherein 0.5≤x≤0.9, 0.1≤y≤0.5. By limiting the chemical formula of the sodium ferrous sulfate matrix and the nickel manganese sulfide, it is beneficial to exert the synergistic effect between the components and further improve the electrochemical performance of the positive electrode material.

[0039] In some embodiments, the particle size of the modified sodium ferrous sulfate positive electrode material is 3 to 8 μm. By limiting the particle size of the modified sodium ferrous sulfate positive electrode material to the above range, it is ensured that the positive electrode material has sufficient exposed active sites to improve the electrochemical performance of the positive electrode material.

[0040] The second aspect of the present invention provides a method for preparing a modified sodium ferrous sulfate positive electrode material, comprising the following steps:

[0041] Step S1, mixing carbon nanotubes, organic ligands, ferric nitrate and an organic solvent, and performing a first heat treatment to obtain a carbon nanotube / iron-based MOF composite material;

[0042] Step S2, mixing hexamethylenetetramine, nickel salt, manganese salt and water, and subjecting the mixture to a second heat treatment to obtain nickel-manganese-based hydroxide; mixing the nickel-manganese-based hydroxide, sodium sulfide and water, and subjecting the mixture to a third heat treatment to obtain nickel-manganese sulfide;

[0043] Step S3, solid-phase mixing the sodium source, ferrous sulfate, and ammonium sulfate, and obtaining a sodium ferrous sulfate material after sintering treatment; mixing the sodium ferrous sulfate material, the carbon nanotube / iron-based MOF composite material, nickel manganese sulfide and water, and performing a fourth heat treatment to obtain a modified sodium ferrous sulfate positive electrode material.

[0044] In the above preparation method, in step S1, iron-based MOF crystals are in situ grown on the surface of carbon nanotubes by a liquid phase method, so that the iron-based MOF and the carbon nanotubes are evenly dispersed, the interface interaction of the composite material is enhanced, and the performance advantages of the carbon nanotubes and iron-based MOF materials are maximized, thereby improving the sodium ion diffusion rate, electronic conductivity, thermal stability and chemical inertness of the positive electrode material, which helps to improve the specific capacity and cycle performance.

[0045] Before the first heat treatment, ultrasonic treatment is also included to make the raw materials dispersed evenly. After the first heat treatment, the product is also subjected to washing and drying, wherein the washing treatment includes water washing and alcohol washing, that is, washing with water first and then washing with alcohol. For example, carbon nanotubes, organic ligands, ferric nitrate and organic solvent are mixed, ultrasonically treated, and then transferred into a high-pressure reactor for the first heat treatment. After the reaction is completed, the carbon nanotube / iron-based MOF composite material is obtained after water washing, alcohol washing and drying.

[0046] In step S2, bimetallic sulfide is synthesized by a liquid phase method. In the second heat treatment process, nickel salt and manganese salt undergo a coprecipitation reaction in the liquid phase to form nickel manganese hydroxide. In the third heat treatment, nickel manganese hydroxide undergoes a replacement reaction with sodium sulfide to form nickel manganese sulfide, which greatly improves the electronic conductivity and improves the specific capacity and cycle performance through the synergistic effect of the bimetal.

[0047] Specifically, the second heat treatment and the third heat treatment can be carried out in a high-pressure reactor, and after the second heat treatment and the third heat treatment, the product is also subjected to washing and drying. For example, hexamethylenetetramine, nickel salt, manganese salt and water are mixed for the second heat treatment, and nickel-manganese-based hydroxide is obtained after centrifugation, washing and drying; it is dispersed in deionized water, sodium sulfide is added, and the third heat treatment is carried out, and nickel-manganese sulfide is obtained after centrifugation, washing and drying.

[0048] In step S3, the sodium ferrous sulfate material is first prepared by solid phase sintering, and then the carbon nanotube / iron-based MOF composite material and nickel manganese sulfide are composited on the surface of the sodium ferrous sulfate material through a fourth heat treatment in the liquid phase, thereby finally forming a modified sodium ferrous sulfate positive electrode material.

[0049] Specifically, the sintering treatment can be carried out in a tubular furnace. For example, after the sodium source, ferrous sulfate and ammonium sulfate are mixed in the solid phase, they are placed in a tubular furnace under a nitrogen atmosphere and sintered at a high temperature to obtain a matrix material; the matrix material is dispersed in deionized water, and the carbon nanotube / iron-based MOF material synthesized in step S1 and the nickel manganese sulfide synthesized in step S2 are added, and a fourth heat treatment is carried out to compound the three together. After the reaction is completed, the modified sodium ferrous sulfate positive electrode material is obtained after centrifugation, washing and drying.

[0050] The present invention does not limit the specific types of each preparation raw material. For example, in some embodiments, the organic ligand includes at least one of phthalic acid, isophthalic acid, and trimesic acid; and / or the organic solvent includes at least one of methanol, ethylene glycol, and N,N-dimethylformamide; and / or the nickel salt includes at least one of nickel nitrate, nickel acetate, and nickel sulfate; and / or the manganese salt includes at least one of manganese nitrate, manganese acetate, and manganese sulfate; and / or the sodium source includes at least one of sodium oxide, sodium hydroxide, sodium carbonate, and sodium nitrate.

[0051] The present invention does not limit the addition amount of each preparation raw material, and can be adjusted according to actual needs.

[0052] For example, in some embodiments, the molar ratio of carbon nanotubes, ferric nitrate, and organic ligands is (10-15):1:(0.8-1), for example, the molar ratio of carbon nanotubes and ferric nitrate is 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, or a range consisting of any two thereof, and the molar ratio of ferric nitrate and organic ligands is 1:0.8, 1:0.9, 1:1, or a range consisting of any two thereof. By controlling the molar ratio of carbon nanotubes, ferric nitrate, and organic ligands, the iron-based MOF and carbon nanotubes can be further uniformly dispersed, thereby enhancing the interface interaction of the composite material.

[0053] In some embodiments, the molar ratio of hexamethylenetetramine, nickel salt and manganese salt is (10-15):1:(0.1-1), for example, the molar ratio of hexamethylenetetramine and nickel salt is 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 or a range consisting of any two thereof, and the molar ratio of nickel salt to manganese salt is 1:0.1, 1:0.2, 1:0.3, 1:0.5, 1:0.8, 1:1 or a range consisting of any two thereof. By regulating the molar ratio of hexamethylenetetramine, nickel salt and manganese salt, nickel ions and manganese ions can be converted into nickel manganese hydroxide to the maximum extent.

[0054] In some embodiments, the molar ratio of nickel manganese-based hydroxide to sodium sulfide is 1:(0.5-1), for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or a range composed of any two of them. By limiting the molar ratio of nickel manganese-based hydroxide to sodium sulfide, the amount of hydroxide converted to sulfide can be controlled, thereby taking into account both the specific capacity and cycle performance of the positive electrode material.

[0055] By limiting the molar ratio of the sodium source, ferrous sulfate and ammonium sulfate, sodium ferrous sulfate materials with different stoichiometric ratios can be prepared. In some embodiments, the molar ratio of the sodium element in the sodium source, ferrous sulfate and ammonium sulfate is (2.06-2.12):2:3, for example, 2.06:2:3, 2.08:2:3, 2.1:2:3, 2.12:2:3 or a range composed of any two of them. By limiting the molar ratio of the sodium source, ferrous sulfate and ammonium sulfate within the above range, sodium ferrous sulfate with a chemical formula of Na2Fe2(SO4)3 can be prepared.

[0056] In some embodiments, the molar ratio of sodium ferrous sulfate, carbon nanotube / iron-based MOF composite material and nickel manganese sulfide is 1: (0.03-0.08): (0.03-0.05), for example, the molar ratio of sodium ferrous sulfate and carbon nanotube / iron-based MOF composite material is 1: 0.03, 1: 0.04, 1: 0.05, 1: 0.06, 1: 0.07, 1: 0.08 or any two thereof, and the molar ratio of carbon nanotube / iron-based MOF composite material and nickel manganese sulfide is 1: 0.03, 1: 0.04, 1: 0.05 or any two thereof. By limiting the molar ratio of sodium ferrous sulfate, carbon nanotube / iron-based MOF composite material and nickel manganese sulfide, positive electrode materials with different first support and second support loadings can be prepared.

[0057] The present invention does not limit the reaction conditions in each step, as long as the desired product is formed. In some embodiments, the temperature of the first heat treatment is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C or any two thereof in the range, and the time is 4-8h, for example, 4h, 5h, 6h, 7h, 8h or any two thereof in the range; and / or, the temperature of the second heat treatment is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C or any two thereof in the range, and the time is 4-8h, for example, 4h, 5h, 6h, 7h, 8h or any two thereof in the range; and / or, the temperature of the third heat treatment is 140-200°C, for example, 140°C, 150°C, 160°C, 170°C, 180°C, 200°C or any two thereof in the range, and the time is 4-12 h, for example, 4h, 5h, 6h, 7h, 8h, 10h, 12h or a range consisting of any two of them; and / or, the sintering treatment is carried out under an inert atmosphere at a temperature of 800-1200°C, for example, 800°C, 900°C, 1000°C, 1100°C, 1200°C or a range consisting of any two of them, and the time is 10-30h, for example, 10h, 15h, 20h, 25h, 30h or a range consisting of any two of them, and the inert atmosphere includes at least one of nitrogen and argon; and / or, the temperature of the fourth heat treatment is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C or a range consisting of any two of them, and the time is 4-8h, for example, 4h, 5h, 6h, 7h, 8h or a range consisting of any two of them.

[0058] The third aspect of the present invention provides a sodium ion battery, comprising the modified sodium ferrous sulfate positive electrode material provided by the first aspect or the modified sodium ferrous sulfate positive electrode material prepared by the preparation method provided by the second aspect.

[0059] Due to the inclusion of the modified sodium iron sulfate positive electrode material, the sodium ion battery of the present invention has excellent electrochemical properties, such as specific capacity and cycle performance.

[0060] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0061] Example 1

[0062] The preparation of the modified sodium ferrous sulfate positive electrode material of this embodiment includes the following steps:

[0063] Step S1, dispersing 0.1 mol of carbon nanotubes, 0.01 mol of phthalic acid, and 0.01 mol of ferric nitrate in 100 mL of N,N-dimethylformamide (DMF), and subjecting the mixture to ultrasonic reaction for 0.5 h, and then transferring the mixture to a high-pressure reactor and heating the reaction mixture at 80° C. for 8 h. After the reaction is completed, the mixture is washed with water, washed with alcohol, and dried to obtain a carbon nanotube / Fe-MOF nanocomposite material;

[0064] Step S2, dissolving 0.1 mol hexamethylenetetramine, 0.01 mol nickel nitrate and 0.005 mol manganese nitrate in 50 mL deionized water, transferring the mixture into a high pressure reactor and heating the mixture at 80° C. for 8 h, centrifuging, washing and drying the mixture after the reaction to obtain a layered nickel manganese-based hydroxide; dispersing the mixture in 50 mL deionized water, adding 0.01 mol sodium sulfide, heating the mixture at 160° C. for 10 h, centrifuging, washing and drying the mixture to obtain a NiMn-S-based nanomaterial;

[0065] Step S3, after solid-phase mixing 0.104 mol of sodium oxide, 0.2 mol of ferrous sulfate, and 0.3 mol of ammonium sulfate, placing them in a tubular furnace under a nitrogen atmosphere and sintering them at 950°C for 20 hours to obtain a Na2Fe2(SO4)3 matrix material; 0.1 mol of the Na2Fe2(SO4)3 matrix material is dispersed in 100 mL of deionized water, and 0.005 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 and 0.003 mol of the NiMn-S-based nanomaterial synthesized in step S2 are added to carry out a composite reaction. After the reaction is completed, the modified sodium ferrous sulfate positive electrode material of this embodiment is obtained after centrifugation, washing, and drying.

[0066] Example 2

[0067] The preparation of the modified sodium ferrous sulfate positive electrode material of this embodiment includes the following steps:

[0068] Step S1, dispersing 0.1 mol carbon nanotubes, 0.01 mol phthalic acid, and 0.01 mol ferric nitrate in 100 mL of DMF, and after ultrasonic reaction for 0.5 h, transferring it into a high-pressure reactor for heating reaction at 80° C. for 8 h. After the reaction is completed, washing with water, washing with alcohol, and drying to obtain a carbon nanotube / Fe-MOF nanocomposite material.

[0069] Step S2, dissolving 0.1 mol hexamethylenetetramine, 0.01 mol nickel nitrate and 0.005 mol manganese nitrate in 50 mL deionized water, transferring the mixture into a high pressure reactor and heating the mixture at 80° C. for 8 h, centrifuging, washing and drying the mixture after the reaction to obtain a layered nickel manganese-based hydroxide; dispersing the mixture in 50 mL deionized water, adding 0.01 mol sodium sulfide, heating the mixture at 160° C. for 10 h, centrifuging, washing and drying the mixture to obtain a NiMn-S-based nanomaterial;

[0070] Step S3, after solid-phase mixing 0.104 mol of sodium oxide, 0.2 mol of ferrous sulfate, and 0.3 mol of ammonium sulfate, placing them in a tubular furnace under a nitrogen atmosphere and sintering them at 950°C for 20 hours to obtain a Na2Fe2(SO4)3 matrix material; 0.1 mol of the Na2Fe2(SO4)3 matrix material is dispersed in 100 mL of deionized water, and 0.003 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 and 0.005 mol of the NiMn-S-based nanomaterial synthesized in step S2 are added to carry out a composite reaction. After the reaction is completed, the modified sodium ferrous sulfate positive electrode material of this embodiment is obtained after centrifugation, washing, and drying.

[0071] Example 3

[0072] The difference from Example 1 is that in step S3, 0.007 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 and 0.003 mol of the NiMn-S-based nanomaterial synthesized in step S2 are added.

[0073] Example 4

[0074] The difference from Example 1 is that in step S3, 0.008 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 and 0.003 mol of the NiMn-S-based nanomaterial synthesized in step S2 are added.

[0075] Example 5

[0076] The difference from Example 1 is that in step S3, 0.002 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 and 0.003 mol of the NiMn-S-based nanomaterial synthesized in step S2 are added.

[0077] Example 6

[0078] The difference from Example 1 is that in step S3, 0.003 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 and 0.002 mol of the NiMn-S-based nanomaterial synthesized in step S2 are added.

[0079] Example 7

[0080] The difference from Example 1 is that in step S3, 0.01 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 and 0.01 mol of the NiMn-S-based nanomaterial synthesized in step S2 are added.

[0081] Comparative Example 1

[0082] After solid-phase mixing of 0.104 mol of sodium oxide, 0.2 mol of ferrous sulfate and 0.3 mol of ammonium sulfate, the mixture was placed in a tubular furnace and sintered at 950° C. for 20 hours under a nitrogen atmosphere to obtain the Na2Fe2(SO4)3 positive electrode material of this comparative example.

[0083] Comparative Example 2

[0084] The difference from Example 1 is that step S2 is omitted, and in step S3, only 0.005 mol of the carbon nanotube / Fe-MOF nanocomposite material synthesized in step S1 is added.

[0085] Comparative Example 3

[0086] The difference from Example 1 is that step S1 is omitted, and in step S3, only 0.003 mol of the NiMn-S-based nanomaterial synthesized in step S2 is added.

[0087] Test example

[0088] 1. Battery Assembly

[0089] The prepared products of the embodiment and the comparative example were used as positive electrode materials. The positive electrode material, acetylene black (AB), and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone (NMP) was used as a solvent. The mixture was placed in a beaker and stirred at a speed of 800 r / min for 2 hours to obtain a slurry. The slurry was coated on a current collector aluminum foil using an automatic coating machine, placed flat on a tempered glass and dried in a vacuum drying oven at 85°C for 4 hours, and punched into sheets with a diameter of 12 The electrode piece of mm was then dried at 105°C in a vacuum drying oven for 4 h, placed in a glove box with an argon atmosphere and a water and oxygen content of less than 0.1 ppm for 4 h to reduce the moisture adsorbed by the electrode piece during the transfer process, and then assembled into a CR2032 button battery in the glove box; the metallic sodium was rolled into thin sheets and punched into 14 mm round sodium sheets as the negative electrode, 1 mol / L NaClO4 solution was used as the electrolyte, and a glass fiber membrane with a diameter of 16 mm was used as the diaphragm.

[0090] 1. Sodium ion diffusion coefficient (conductivity) test

[0091] The sodium ion diffusion coefficient (conductivity) test is as follows: the above positive electrode materials are assembled into button cells and an AC impedance test is performed under the test conditions of a disturbance voltage of 5 mV and a test frequency of 0.01 Hz to 100 kHz.

[0092] 2. Electrochemical performance test

[0093] After aging the assembled battery for 12 hours, the first charge and discharge capacity test was performed. The test conditions were: charge to 4V at 0.1C, stand for 1 minute, and then discharge to 2.2V at 0.1C. The charge and discharge curves were obtained, and the first discharge specific capacity D0 from 2.2 to 4V was recorded respectively.

[0094] The battery was charged and discharged at 25°C using a battery charge and discharge tester. The battery was charged to 4V at 0.1C constant current, and then discharged to 2.2V at 0.1C constant current after standing for 1 minute. This cycle was repeated for 5 cycles. After standing for 1 minute, the battery was charged to 4V at 2C constant current. After standing for 1 minute, the battery was discharged to 2.2V at 2C constant current. This cycle was repeated for 100 cycles. The discharge capacity Q1 at the first cycle under 2C conditions and the discharge capacity Q at the 100th cycle under 2C conditions were determined. 100 , calculate the capacity retention rate after 100 cycles according to the following formula:

[0095] Capacity retention rate Q = Q 100 / Q1×100%.

[0096] 3. Structural stability test

[0097] The criterion is whether the primary particles in the positive electrode material are broken after 100 cycles under 2C conditions, and TEM is used to test whether the material particles have cracks.

[0098] The test results are shown in Table 1.

[0099] Table 1

[0100]

[0101] according to Figures 1 to 3 It can be seen from the SEM image of the modified sodium ferrous sulfate positive electrode material in Example 1 that the positive electrode material is in a micron block structure, the material particle size is evenly distributed, the D50 particle size is 3 to 8 μm, and there is no obvious small particle distribution on the surface of the material, proving that the multi-component nanomaterial composite layer is completely composited on the surface of the main material and is not separately dispersed in the external area. Figure 4 and Figure 5 It can be seen that the particles of the modified sodium ferrous sulfate positive electrode material of Example 1 have no cracks after the cycle treatment, while the particles of the positive electrode material of Comparative Example 1 have cracks, which indicates that the modified sodium ferrous sulfate positive electrode material of the present invention has excellent structural stability.

[0102] It can be seen from Table 1 that applying the modified ferrous sulfate positive electrode material provided by the present invention to a sodium ion battery can effectively improve the specific capacity and cycle performance of the battery.

[0103] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified sodium ferrous sulfate positive electrode material, characterized in that: The invention comprises a sodium ferrous sulfate matrix and a carbon nanotube / iron-based MOF composite material and nickel manganese sulfide loaded on the sodium ferrous sulfate matrix.

2. The modified sodium ferrous sulfate positive electrode material according to claim 1, characterized in that: In the modified sodium ferrous sulfate positive electrode material, the molar ratio of the sodium ferrous sulfate matrix to the carbon nanotube / iron-based MOF composite material is 1: (0.03~0.08); and / or, the molar ratio of the sodium ferrous sulfate matrix to the nickel manganese sulfide is 1:(0.03~0.05); and / or, the carbon nanotube / iron-based MOF composite material includes carbon nanotubes and an iron-based MOF material synthesized in situ on the carbon nanotubes, wherein the molar ratio of the carbon nanotubes to the iron element in the iron-based MOF material is (10~15):

1.

3. The modified sodium ferrous sulfate positive electrode material according to claim 2, characterized in that: The preparation method of the carbon nanotube / iron-based MOF composite material comprises: mixing carbon nanotubes, organic ligands, ferric nitrate and an organic solvent, and performing a heating treatment to in-situ synthesize the iron-based MOF material on the carbon nanotubes to obtain the carbon nanotube / iron-based MOF composite material.

4. The modified sodium ferrous sulfate positive electrode material according to claim 1 or 2, characterized in that: The chemical formula of the sodium ferrous sulfate matrix is ​​Na2Fe2(SO4)3; the chemical formula of the nickel manganese sulfide is Ni x Mn y S2, where 0.5≤x≤0.9, 0.1≤y≤0.

5.

5. The modified sodium ferrous sulfate positive electrode material according to claim 1 or 2, characterized in that: The D50 particle size of the modified sodium ferrous sulfate positive electrode material is 3 to 8 μm.

6. A method for preparing the modified sodium ferrous sulfate positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, mixing carbon nanotubes, organic ligands, ferric nitrate and an organic solvent, and subjecting the mixture to a first heat treatment to obtain a carbon nanotube / iron-based MOF composite material; Step S2, mixing hexamethylenetetramine, nickel salt, manganese salt and water, and subjecting the mixture to a second heat treatment to obtain nickel-manganese-based hydroxide; mixing the nickel-manganese-based hydroxide, sodium sulfide and water, and subjecting the mixture to a third heat treatment to obtain nickel-manganese sulfide; Step S3, solid-phase mixing the sodium source, ferrous sulfate, and ammonium sulfate, and obtaining a sodium ferrous sulfate material after sintering treatment; mixing the sodium ferrous sulfate material, the carbon nanotube / iron-based MOF composite material, and the nickel manganese sulfide with water, and performing a fourth heat treatment to obtain the modified sodium ferrous sulfate positive electrode material.

7. The preparation method according to claim 6, characterized in that: The organic ligand includes at least one of phthalic acid, isophthalic acid, and trimesic acid; and / or the organic solvent includes at least one of methanol, ethylene glycol, and N,N-dimethylformamide; and / or the nickel salt includes at least one of nickel nitrate, nickel acetate, and nickel sulfate; and / or the manganese salt includes at least one of manganese nitrate, manganese acetate, and manganese sulfate; and / or the sodium source includes at least one of sodium oxide, sodium hydroxide, sodium carbonate, and sodium nitrate.

8. The preparation method according to claim 6, characterized in that: The molar ratio of the carbon nanotube, the ferric nitrate and the organic ligand is (10-15): 1: (0.8-1); and / or, the molar ratio of the hexamethylenetetramine, the nickel salt and the manganese salt is (10-15):1:(0.1-1); and / or, the molar ratio of the nickel-manganese-based hydroxide to the sodium sulfide is 1:(0.5-1); and / or, the molar ratio of the sodium element in the sodium source, the ferrous sulfate and the ammonium sulfate is (2.06-2.12):2:3; and / or, the molar ratio of the sodium ferrous sulfate, the carbon nanotube / iron-based MOF composite material and the nickel-manganese sulfide is 1: (0.03~0.08):(0.03~0.05)。 9. The preparation method according to claim 6, characterized in that: The temperature of the first heat treatment is 60-100°C, and the time is 4-8 hours; and / or, the temperature of the second heat treatment is 60-100°C, and the time is 4-8 hours; and / or, the temperature of the third heat treatment is 140-200°C, and the time is 4-12 hours; and / or, the sintering treatment is carried out under an inert atmosphere, the temperature is 800-1200°C, and the time is 10-30 hours; and / or, the temperature of the fourth heat treatment is 40-60°C, and the time is 4-8 hours.

10. A sodium ion battery, characterized in that: The invention comprises the modified sodium ferrous sulfate positive electrode material according to any one of claims 1 to 5 or the modified sodium ferrous sulfate positive electrode material prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Cited By

  • Sodium ion battery and preparation method and application thereof

    CN119905645A

  • A sodium-ion battery and a preparation method and application thereof

    CN119905645B